Investigation of Technogenic Soil Properties in Potassium Production - B. A. Bogatov; S. F, Shemet (Наука и техника)
The paper contains the results of experimental investigations of physical and mechanical properties of technogenic slime soil. The experimental data have made it possible to obtain mathematical dependences of moisture, adhesion, internal friction angle, filtration coefficient on time usage of slime soil as construction material for slime storage dikes.